Developing Student Worksheet of Cylinder Using Techno-Ethno-Realistic Mathematics Education Assisted by Augmented Reality - Farida Nursyahidah; Irkham Ulil Albab; Maya Rini Rubowo (SJME (Supremum Journal of Mathematics Education), 2026)
Mastery of cylinder material is essential for strengthening students’ spatial reasoning and understanding of curved-3D shapes; however, prior research shows persistent difficulties in learning 3D shapes one of them is thc cylinder. These difficulties are often exacerbated by limited use of innovative, contextual, and technology-supported learning materials. To address these challenges, this research integrates three key components ethnomathematics, RME, and technology to support dynamic visualization of cylindrical shapes. This study aims to develop a student worksheet using the Techno-Ethno-Realistic Mathematics Education (TE-RME) approach assisted by AR for learning cylinder concepts in junior secondary school. This study uses a design research methodology in two stages, namely a preliminary study and formative evaluation. The subjects of this study were 33 ninth-grade students of junior high school in Semarang. Data collected through observations, tests, and interviews were analyzed descriptively. This study produced a student activity sheet on cylinder material, which was combined with animated video and AR media whose effectiveness and efficiency align with the characteristics of the TE-RME approach. Based on these findings, it can be concluded that the TE-RME-based student activity sheet combined with animated video and AR media is efficient and effective in helping students develop conceptual understanding and problem-solving skills. The integration of animated video and AR media and the TE-RME approach reflects a commitment to innovation and continuous development of effective learning designs that promote inclusive, equitable, and meaningful learning experiences.